PENGARUH PEMBELAJARAN BERBASIS MASALAH BERBANTUAN QUIZIZZ TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN MOTIVASI BELAJAR SISWA KELAS IV SEKOLAH DASAR DI GUGUS DAHLIA JAKARTA BARAT - Linda Tresna Setiawati; Sardjiyo; Mestika Sekarwinahyu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Problem Based Learning (PBL) is a learning model grounded in contextual problems aligned with students' needs and characteristics. This research aims to determine the effect of problem-based learning assisted by Quizizz on the mathematical critical thinking skills and learning motivation of fourth-grade elementary school students in Gugus Dahlia, West Jakarta. The research employs a quantitative method with survey techniques. The population consists of fourth-grade students from State Elementary Schools in Gugus Dahlia, Palmerah District, West Jakarta Administrative City, totaling 302 students. Using Purposive Sampling techniques, 172 sample respondents were selected. The research instruments include a questionnaire for the Problem Based Learning variable assisted by Quizizz (X), learning outcomes tests via Quizizz for the Mathematical Critical Thinking Ability variable (Y1), and a questionnaire for the Learning Motivation variable (Y2). Data analysis was conducted using SPSS, including prerequisite tests such as normality, homogeneity, multicollinearity, heteroscedasticity, error normality, and linearity tests. Hypothesis tests comprised correlation analysis, regression analysis, and the coefficient of determination. The heteroscedasticity test value exceeded 0.05 with a significant value of 0.379, indicating that problem-based learning with Quizizz can enhance students' mathematical critical thinking abilities. The Spearman's rho correlation test yielded a significant value of 0.75, surpassing the 0.05 threshold, suggesting that the regression model for variable X against Y2 is not affected by heteroscedasticity. Therefore, this research concludes that problem-based learning assisted by Quizizz significantly influences and maintains linearity in student learning motivation. The implication is that teachers should create appropriate learning environments to provide liberating education by selecting suitable learning models, methods, and media tailored to students' needs and abilities.